Descriptional complexity of formal systems : 21st IFIP WG 1.02 International Conference, DCFS 2019, Košice, Slovakia, July 17–19, 2019, proceedings /: 21st IFIP WG 1.02 International Conference, DCFS 2019, Košice, Slovakia, July 17–19, 2019, proceedings. (2019) - Unknown
No abstract available